Analysis of Directive Speech Actions in the Liam and Laila Films and its Relevance as Teaching Material in Class XI SMA - Suryo Daru Santoso; Ria Saputri (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this study is to describe: (1) the form and function of directive speech acts contained in the Liam and Laila film conversations and (2) the relevance of directive speech acts in Liam and Laila films as teaching material in class XI of high school. This research is a qualitative descriptive type, the object of research is speech in conversation in the film Liam and Laila which is focused on directive speech act analysis. The data in this study are in the form of utterances which are thought to include forms of directive speech acts taken from conversations in the film Liam and Laila. The data collection techniques used are competent, free listening and note taking techniques, while the data analysis technique uses the matching method. The results showed: (1) the form and function of speech acts include: requests (asking, asking, pressing, and inviting), questions (asking and interrogating), commands (willing, asking, demanding, and requiring), prohibitions (prohibiting and limiting) ), granting permission (approving, allowing and forgiving), advice (advising and warning). (2) The directive speech acts in the Liam and Laila films can be used as teaching materials for class XI high school students in KD 3.19 Identifying the contents and language of the drama that is read or watched. Abstrak Tujuan penelitian ini adalah untuk mendeskripsikan: (1) bentuk dan fungsi tindak tutur direktif yang terdapat pada percakapan film Liam dan Laila dan (2) relevansi tindak tutur direktif dalam film Liam dan Laila sebagai bahan ajar di kelas XI SMA. Penelitian ini berjenis deskriptif kualitatif, objek penelitian berupa tuturan-tuturan dalam percakapan pada film Liam dan Laila yang difokuskan pada analisis tindak tutur direktif. Data dalam penelitian ini berupa tuturan yang diduga termasuk bentuk tindak tutur direktif yang diambil dari percakapan pada film Liam dan Laila. Adapun teknik pengumpulan data yang digunakan adalah teknik simak bebas libat cakap dan teknik catat, sedangkan teknik analisis datanya menggunakan metode padan. Hasil penelitian menunjukkan: (1) bentuk dan fungsi tindak tutur meliputi: permintaan (meminta, memohon, menekan, dan mengajak), pertanyaan (bertanya dan menginterogasi), perintah (menghendaki, menyuruh, menuntut, dan mensyaratkan), larangan (melarang dan membatasi), pemberia izin (menyetujui, membolehkan, dan memaafkan), nasihat (menasihati dan memperingatkan). (2) Tindak tutur direktif dalam film Liam dan Laila dapat digunakan sebagai bahan ajar siswa kelas XI SMA pada KD 3.19 Mengidentifikasi isi dan kebahasaan drama yang dibaca atau ditonton. Kata kunci: tindak tutur direktif, film Liam dan Laila, bahan ajar, kelas XI SMA